Numerical simulation of inductive heating in thermoplastic unidirectional cross-ply laminates - de Wit, A. J.; van Hoorn, N.; Straathof, L. S.; Vankan, W. J. (Frontiers in Materials, 2023)
In this work the inductive heating of uni-directional (UD) plies of thermoplastic carbon fiber reinforced polymer (CFRP) laminates is investigated. The focus is on developing a numerical electromagnetic and thermal simulation model that captures the main processes involved in eddy current generation and the heat generation, in particular in the UD plies interface areas. For the electric properties of the plies a measurement technique has been developed to obtain these parameters. Furthermore, to support the modelling of the induction heating equipment and work piece a field measurement of the magnetic field surrounding the coil and work piece has been developed. To compare and validate the electro-magnetic simulation model inductive heating experiments were carried out on several thick composite plates with different ply lay-ups and the measured surface temperatures were compared with the results from the simulation model. The results of this work can be used to support the design of UD-ply laminates to improve their ability to be welded via induction and to assist in pre-determining induction welding equipment settings and heating times.